Organic Farming- A Perspective - Ramanjaneyulu, A. V.; Sarkar, N. C.; Thakur, Ashok K.; Maiti, R. K. (International Journal of Bio-resource and Stress Management, 2013)
The present commercial farming systems, due to intensive involvement of synthetic chemical inputs, have shown negative impacts on human health and ecology. In the recent past, this eyebrow raising issue forced the policy makers, researchers, producers and consumers to find out the healthy and safe alternate ways of farming. Organic farming is one such system that provides healthy food without leaving negative mark on the environment. According to United States Department of Agriculture (USDA), organic farming is the production system which avoids or largely excludes the use of synthetically compounded fertilizers, pesticides, growth regulators, and live stock feed additives…